Normal Renal Function - O'Connor, W. J. author. aut Link
VIII, 434 p.
Keywords: This book has developed from an earlier monograph, 'Renal Function' (1962; London, Edward Arnold). It retains the general purpose of that book in relating the composition of the blood to the volume and com position of the urine of animals, including the new data of the intervening 20 years. As indicated by its title, this new book also has the particular purpose of studying the urine of animals in a normal environment and eating food usual to the species. Renal physiology illustrates a dilemma which arises also in other fields. Advanced technology, harnessed by accumulated experimental skill, now allows detailed investigation of basal processes. Micropuncture experiments have greatly advanced our understanding of the processes of glomerular fil tration and tubular reabsorption and have contribut ed to the wider discussion of the physicochemical nature of the movement of water and ions across cell surfaces. But experiments at microscopic or cell ular level demand experimental conditions in which the systems are abstracted from their natural en vironment, either as isolated perfused preparations or with the anaesthetised animal merely providing support for a tissue left in situ. The arguments from such experiments, important though they are towards understanding the basal processes, readily become remote from the reality of the normal animal.